183 Improving Wellbeing Among UK Doctors Redeployed During Thecovid-19 Pandemic. (12th October 2021) - Faderani, R; Monks, M; Peprah, D; Colori, A; Allen, L; Amphlett, A; Edwards, M
Abstract: Background: In response to the COVID-19, the NHS has implemented significant workforce changes to manage the increased and changing demand on healthcare services. We aimed to investigate the impact of such changes on the wellbeing of redeployed doctors. Method: We conducted a survey at three NHS trusts over 2 weeks during the peak of the pandemic, asking redeployed doctors to rate their morale, work–life balance, perceived support and safety, and to voice concerns. Results: 172 redeployed doctors responded to the survey. On exploring morale, 114 (66.3%) respondents felt confident in their new role, 113 (65.7%) felt satisfied or neutral with their new role and only 54 (31.4%) felt stressed at work. 114 (66.3%) doctors felt valued by their team and 136 (79%) felt valued by the general public. 111 (64.5%) had noticed an increase in the length of breaks and 153 (89%) felt that their rotas provided sufficient respite. 95 respondents (55.2%) did not feel confident in the Public Health personal protective equipment (PPE) guidance and similarly 94 (54.7%) did not feel safe while wearing PPE. The three most common concerns were training opportunities – 105 (61%), PPE – 99 (57.6%) and family health – 95 (55.2%). Conclusions: Our findings suggest that, among the doctors surveyed, morale is higher than might be expected, with doctors feeling valued, confident, and well rested in their new role. Concerns about training opportunities/career progression, PPE and family safety need to be addressed to minimise the adverse effects on doctor's wellbeing due to redeployment.